Functional characterization of heat‐shock protein 90 from Oryza sativa and crystal structure of its N‐terminal domain. Issue 6 (1st June 2015) - Raman, Swetha; Suguna, Kaza
<x xml:space="preserve">Abstract</x> Heat‐shock protein 90 (Hsp90) is an ATP‐dependent molecular chaperone that is essential for the normal functioning of eukaryotic cells. It plays crucial roles in cell signalling, cell‐cycle control and in maintaining proteome integrity and protein homeostasis. In plants, Hsp90s are required for normal plant growth and development. Hsp90s are observed to be upregulated in response to various abiotic and biotic stresses and are also involved in immune responses in plants. Although there are several studies elucidating the physiological role of Hsp90s in plants, their molecular mechanism of action is still unclear. In this study, biochemical characterization of an Hsp90 protein from rice (Oryza sativa; OsHsp90) has been performed and the crystal structure of its N‐terminal domain (OsHsp90‐NTD) was determined. The binding of OsHsp90 to its substrate ATP and the inhibitor 17‐AAG was studied by fluorescence spectroscopy. The protein also exhibited a weak ATPase activity. The crystal structure of OsHsp90‐NTD was solved in complex with the nonhydrolyzable ATP analogue AMPPCP at 3.1 Å resolution. The domain was crystallized by cross‐seeding with crystals of the N‐terminal domain of Hsp90 from Dictyostelium discoideum, which shares 70% sequence identity with OsHsp90‐NTD. This is the second reported structure of a domain of Hsp90 from a plant source.